Pentocin MQ1: A Novel, Broad-Spectrum, Pore-Forming Bacteriocin From Lactobacillus pentosus CS2 With Quorum Sensing Regulatory Mechanism and Biopreservative Potential - Wayah, Samson B.; Philip, Koshy (Frontiers in Microbiology, 2018)
Micrococcus luteus, Listeria monocytogenes and Bacillus cereus are major food-borne pathogenic and spoilage bacteria. Emergence of antibiotic resistance and consumer demand for foods containing less of chemical preservatives led to a search for natural antimicrobials. A study aimed at characterizing, investigating the mechanism of action and regulation of biosynthesis and evaluating the biopreservative potential of pentocin from Lactobacillus pentosus CS2 was conducted. Pentocin MQ1 is a novel bacteriocin isolated from Lactobacillus pentosus CS2 of coconut shake origin. The purification strategy involved adsorption-desorption of bacteriocin followed by RP-HPLC. It has a molecular weight of 2110.672 Da as determined by MALDI-TOF mass spectrometry and a molar extinction value of 298.82 M-1 cm-1. Pentocin MQ1 is not plasmid-borne and its biosynthesis is regulated by a quorum sensing mechanism. It has a broad spectrum of antibacterial activity, exhibited high chemical, thermal and pH stability but proved sensitive to proteolytic enzymes. It is potent against Micrococcus luteus, Bacillus cereus and Listeria monocytogenes at micromolar concentrations. It is quick-acting and exhibited a bactericidal mode of action against its targets. Target killing was mediated by pore formation. We report for the first time membrane permeabilization as a mechanism of action of the pentocin from the study against Gram-positive bacteria. Pentocin MQ1 is a cell wall-associated bacteriocin. Application of pentocin MQ1 improved the microbiological quality and extended the shelf life of fresh banana. This is the first report on the biopreservation of banana using bacteriocin. These findings place pentocin MQ1 as a potential biopreservative for further evaluation in food and medical applications.